Clinical Study of 100cases of Caesarean Section in Tairunnessa Memorial Medical College & Hospital. Gazipur (Medicine Today, 2017)
To find out the common indications of caesarean section and complications of this operation, both for mother and baby. This observational study was carried out on 100 cases of caesarean sections, who were operated in the Department of Obstetrics & Gynaecology, Tairunnessa Memorial Medical College & Hospital. Previous caesarean section and oligohydroamnios with fetal distress contribute the major causes of caesarean section. Contribute the major causes of caesarean section. Common complications are UTI, wound infection. Indications of caesarean section should be properly identified to decrease the unnecessary operation, which ultimately decrease indication of previous caesarean section. Maintenance of proper asepsis would avoid the complications of this operation.Medicine Today 2016 Vol.28(2): 66-68